Sequencing Multiple Cotton Genomes Reveals Complex Structures and Lays Foundation for Breeding - Pan, Yuxin; Meng, Fanbo; Wang, Xiyin (Frontiers in Plant Science, 2020)
Cotton is a major fiber plant, which provides raw materials for clothing, protecting humans from the harsh environment of cold or hot weathers, enriching the culture and custom of human societies. Due to its importance, the diploid and tetraploid genomes of different cotton plants have been repeatedly sequenced to obtain their complete genome sequences. These valuable genome data disclosed the evolutionary past of the cotton plants, which were recursively affected by polyploidization, with a decaploidization contributing to the formation of Gossypium, and a neo-tetraploidization contributing to the formation of nowadays widely cultivated cotton. Post-polyploidization genome instability contributed the structural changes of the genomes, such as illegitimate recombination and gene conversion, and accumulation of repetitive sequences, and functional innovation accompanied by elevated evolutionary rates of genes. The availability of whole-genome sequences have now paved the way to identify and clone functional genes, e.g., those relating to fiber development, and breeding efforts to cultivate cottons to produce high-yield, high-quality fibers, and to resist environmental and biological stress.